A combined approach of robot-assisted laparoscopic pyeloplasty and flexible endoscopy to treat concomitant ureteropelvic junction obstruction and calyceal stones in children: Technical considerations and review of the literature - Wong, Yuenshan Sammi; Lo, Ka Lun; Pang, Kristine Kit Yi; Tam, Yuk Him (Frontiers in Pediatrics, 2022)
The management of children with concomitant ureteropelvic junction (UPJ) obstruction and calyceal stones remains challenging. The various treatment options available for pediatric nephrolithiasis may require multiple sessions, and the techniques by themselves are not designed for simultaneous correction of UPJ obstruction. Recently, success in combining robot-assisted laparoscopic pyeloplasty (RALP) and flexible endoscopy has been reported by multi-institutional studies to treat children with concomitant UPJ obstruction and renal stones. Given the paucity of technical details of this novel approach in the existing literature, we herein report our techniques to treat two girls aged 6 and 10 years who had concomitant UPJ obstruction and multiple stones in mid- and lower poles calyces. Three robotic ports were used without any assistant ports. A flexible endoscope, either a cystoscope or a single-use ureteroscope, was introduced via the undocked epigastric port to perform nephroscopy and stones removal after the renal pelvis was opened. The rest of the RALP was completed in the usual manner. Technical modifications were employed to facilitate the flexible endoscope to examine the entire calyceal system. Both patients underwent successful surgical procedures by the combined approach without any intra- or post-operative complications. Three and 14 stones were removed from each of the patients respectively. Postoperative investigations demonstrated successful correction of UPJ obstruction and complete stone clearance in both patients. A combined approach of RALP and flexible endoscopy is a safe and effective technique to treat concurrent UPJ obstruction and calyceal stones in children.